Leadership, Communication, and Work Motivation in Determining the Success of Professional Organizations - Farhan Saputra (Journal of Law, Politic and Humanities, 2021)
An organization is said to be professional if several indicators indicate the organization is professional. The leadership that regulates or manages the organization is the first indicator of an organization’s professionalism because, without leadership, the organization cannot run and achieve its goals. Then after leadership, there are indicators of communication as a determinant and the professionalism of an organization. Moreover, another critical factor in professional organizations is work motivation, which if an organization has good motivation or goals, the organization will achieve its goals quickly. In his study, a literature review study was produced. This review article is Leadership, Communication, and Work Motivation in determining the success of Professional Organizations. The results of this library research are that: 1) Leaderhip determines the success of Professional Organizations; 2) Communication determines the success of Professional Organizations; 3) Work Motivation determines the success of Professional Organizations.